HUBUNGAN HUBUNGAN PENGETAHUAN IBU HAMIL TENTANG COVID-19 DENGAN PERILAKU PENCEGAHAN PENULARAN COVID-19 DI PUSKESMAS UMBULHARJO 1 KOTA YOGYAKARTA - MELINA, FITRIA (Jurnal Kesehatan Samodra Ilmu (JKSI), 2022)
Background: The global incidence of Covid-19 is 119,791,453 cases with confirmed deaths of around 2,652,966. In Indonesia, 4.9% of pregnant women were positive for COVID-19 from 1,483 cases. Based on data from the DINKES Kota DIY 2021, the number of pregnant women exposed to Covid-19 was 1,498 and who died as many as 67 people and the highest incidence was at the Umbulharjo 1 Health Center Yogyakarta. Purpose: This study aims to determine the relationship between knowledge of pregnant women about Covid-19 and the behavior of preventing transmission of Covid-19 at the Umbulharjo 1 Health Center Yogyakarta. Research Methods: This research is quantitative research, this research uses an analytical survey method with a cross sectional research design. The population in this study were some of the pregnant women in the Umbulharjo 1 Health Center Yogyakarta, amounting to 72 respondents. The sampling technique used was accidental sampling. Analysis of the data used is the Kendall-Tau statistical test. Results: The distribution of the frequency of knowledge of pregnant women about Covid-19 is in the less category as many as 36 people (50%). -19 with Preventive Behavior Covid-19 is in the less category with negative behavior as many as 14 (19.4%) mothers and positive behavior as many as 22 mothers (30.6%). The results of the Kendall-Tau test with <α=0.246 obtained a significant value of 0.005. Conclusion: There is a significant relationship between the knowledge of pregnant women about Covid-19 with behaviors to preventing the covid-19 transmission in Puskesmas Umbulharjo 1 Yogyakarta Keywords: Knowledge, Covid-19